The final warning - Patterson, James, 1947- (Patterson, James, 1947- Maximum Ride ;, 2008)
While on a mission to Antarctica to save the world from global warming, fourteen-year-old Maximum Ride and the other members of the Flock--a band of genetically modified children who can fly--are pursued by their creator, the Uber-Director, who wants to auction them off to the highest bidder.